Synergistic effects of Vachellia nilotica-derived zinc oxide nanoparticles and melatonin on drought tolerance in Fragaria × ananassa - Tauseef Anwar; Alia Safdar; Huma Qureshi; Ejaz Hussain Siddiqi; Naimat Ullah; Muhammad Tahir Naseem; Walid Soufan (BMC Plant Biology)
Abstract This study investigates the synergistic effects of zinc oxide nanoparticles (ZnO NPs) and melatonin (MT) on Fragaria × ananassa (strawberry) plants under drought stress, focusing on growth, fruit biomass, and stress tolerance. ZnO NPs enhance nutrient uptake and stress resistance, while MT regulates growth hormones and boosts photosynthetic efficiency. Seven treatments were evaluated: T1 (no stress, 0.5 g/L ZnO NPs + 0.1 g/L MT), T2 (no stress, 0.5 g/L ZnO NPs), T3 (no stress, 0.1 g/L MT), T4 (drought stress, no application), T5 (drought stress, 0.5 g/L ZnO NPs + 0.1 g/L MT), T6 (drought stress, 0.5 g/L ZnO NPs), and T7 (drought stress, 0.1 g/L MT). Growth and stress parameters included shoot/root length, fruit biomass, bud number, chlorophyll content, oxidative stress markers (H₂O₂, MDA), and antioxidant enzyme activities in the leaves of Fragaria × ananassa. The combined treatment (ZnO NPs + MT) consistently outperformed others, achieving the highest growth metrics under both conditions: shoot length (22.33 ± 1.53 cm non-stress, 15.00 ± 1.53 cm drought), root length (18.67 ± 1.53 cm non-stress, 12.00 ± 1.53 cm drought), and fruit biomass (9.55 ± 0.31 g non-stress, 5.02 ± 0.23 g drought). Bud formation peaked at 3.33 ± 0.58 buds/plant non-stress and 2.00 ± 0.00 buds/plant drought. Under drought, the combined treatment also enhanced chlorophyll content (2.47 ± 0.20 mg/g FW) and significantly reduced H₂O₂ (28.67 ± 2.52 µmol/g FW) and MDA (4.21 ± 0.10 µmol/g FW) levels, while maximizing antioxidant enzyme activities (SOD: 121.67 ± 7.64 U/g FW, POD: 206.33 ± 14.84 U/g FW, CAT: 48.00 ± 3.61 U/g FW). These findings highlight the combined application of ZnO NPs and MT as a promising strategy to enhance growth and stress tolerance in strawberry plants, warranting further research on optimized concentrations, delivery methods, and molecular mechanisms.